Pre-weaning maternal separation increases eating later in life in male and female offspring, but increases brainstem dopamine receptor 1a and 2a only in males. (1st April 2018) - de Souza, Julliet Araújo; da Silva, Matilde Cesiana; de Matos, Rhowena Jane Barbosa; do Amaral Almeida, Larissa Cavalcanti; Beltrão, Luana Cruz; de Souza, Felipe Leitão; de Castro, Raul Manhães; de Souza, Sandra Lopes
Abstract: Maternal separation stress (MS) is a model of early life stress performed by the separation between dam and pups in the first days of life. This model has been associated with eating behavior and dopaminergic system abnormal phenotypes. This study aims to investigate whether maternal separation in the light or dark phase of the circadian cycle promotes phenotypic adjustments in the eating behavior and the dopamine system in both males and females. Lactating Wistar rats were separated from their litters from postnatal day 1 (PND 1) to PND 14 for 6 h in the light or dark phase of the circadian cycle. The groups of female control (FC), male control (MC), female rat separated in the dark (FSD), male rat separated in the dark (MSD), female rat separated in the light (FSL), and male rat separated in the light (MSL) were composed. The assessment of food intake was performed at the age of 120–150 days and the analysis of brainstem drd1a and drd2a dopamine receptors expression at 180 days of life. Maternal separation promoted higher palatable diet intake independent on sex and circadian cycle. On the other hand, drd1a and drd2a dopamine receptors expression were higher only in males separated in the dark phase of the circadian cycle. These findings demonstrate that maternal separation effects on feeding behavior do not depend on sex and circadian cycle, but the effects on dopamine receptors expression depend on sex and circadian cycle.